Fashion patternmaking techniques for children's clothing : dresses, shirts, bodysuits, trousers, shorts, jackets and coats - Donnanno, Antonio (Promopress, 2020)
"Fashion Patternmaking Technique for Kids clothes is the result of 15 years reprints and corrections based in an everyday teaching praxis, which lead to careful studies and ongoing updates taking into account changing needs. As in the other volumes of the series, the author has written a method, simple but at the same time detailed, precise and easy to understand."--Publisher's description